2021
DOI: 10.1155/2021/6230826
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress for the Clinical Application of Circulating Tumor Cells in Prostate Cancer Diagnosis and Treatment

Abstract: Prostate cancer is a life-threatening and highly heterogeneous malignancy. In the past decade, circulating tumor cells (CTCs) have been suggested to play a critical role in the occurrence and progression of prostate cancer. In particular, as the “seed” of the cancer metastasis cascade, CTCs determine numerous biological behaviors, such as tumor invasion into adjacent tissues and migration to distant organs. Many studies have shown that CTCs are necessary in the processes of tumor progression, including tumorig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 109 publications
(74 reference statements)
0
14
0
Order By: Relevance
“…The main features of CTCs are rarity and heterogeneity: This is why separation and enrichment are challenging and represent the main limitation of this approach [ 147 ]. There are several sorting protocols that exploit different features of CTCs, such as volume, density and biomarkers.…”
Section: Tissue and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The main features of CTCs are rarity and heterogeneity: This is why separation and enrichment are challenging and represent the main limitation of this approach [ 147 ]. There are several sorting protocols that exploit different features of CTCs, such as volume, density and biomarkers.…”
Section: Tissue and Methodsmentioning
confidence: 99%
“…For example, the CellSearch ® is an IVD-certified method in US for separation and counting of CTCs and it is based on the detection of epithelial cell adhesion molecule (EpCAM). Unfortunately, since CTCs are heterogeneous and undergo epithelial to mesenchymal transition (EMT) to escape the primary tumor, losing EpCAM and/or cytokeratin expression, this approach is not always ideal to succeed [ 146 , 147 ]. There are other commercially available platforms for CTCs isolation based on different technologies but despite the advantages of each one, there are also many drawbacks, including low cell viability or moderate sensitivity and doubts about accuracy in capturing viable CTCs [ 148 ].…”
Section: Tissue and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Circulating tumor cells (CTC) are tumor cells that are separated from solid tumor lesions which enter the blood circulatory system, where they can be detected in peripheral blood ( Smit et al, 2021 ). There are currently various technologies available that can separate CTC from blood using biophysical methods (deformability, size, density, and surface charge) and/or immunoaffinity status ( Khetani et al, 2018 ; Habli et al, 2020 ; Yang et al, 2021 ). Previous studies have found that the number of CTC in the peripheral blood of patients with CRC after surgery is significantly related to the prognosis ( Rahbari et al, 2010 ; Iinuma et al, 2011 ; Bork et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%